PROFESIONALISME WARTAWAN TELEVISI (Studi Kasus Pada Jurnalis di Batu TV Kota Batu Jawa Timur, Bulan Agustus - September 2012) - , Aryo Prakoso Wibowo; , Dr. Phil. Ana Nadhya Abrar, M.E.S. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Batu Television is one of the local television media that are in the area of Batu, East Java. The quality of human resources in the local television media is not as good as the workers on the national television media. Human resource issues in terms of broadcasting led to a shortage - a shortage of news related to the quality (coverage and editing). The presence of local television as an option for people to get information, entertainment, and education while promoting ethical codes television journalist. News production process is essential to provide news content to the public good. Good News presented by journalists who understand and adhere to the code of ethics of journalists Television journalist is a professional who works by rule or code of journalistic ethics as operational guidelines to maintain public confidence, to uphold the integrity and professionalism